2022
DOI: 10.1161/jaha.121.025828
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sleep Microstructure and Incident Hypertension in a Population‐Based Sample: The HypnoLaus Study

Abstract: Background Poor sleep quality is associated with increased incident hypertension. However, few studies have investigated the impact of objective sleep structure parameters on hypertension. This study investigated the association between sleep macrostructural and microstructural parameters and incident hypertension in a middle‐ to older‐aged sample. Methods and Results Participants from the HypnoLaus population‐based cohort without hypertension at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…However, there is a paucity of research investigating the relationship between sleep microarchitecture and the future development of hypertension in OSA. Berger et al recently reported that low delta power in non-REM sleep is independently associated with the risk of developing hypertension, confirming the previously noted relationship of SWS with incident hypertension [18]. Another study relied on complex feature engineering to examine 27 unselected clinical predictors, encompassing demographic characteristics, lifestyle behaviors, and OSA severity (apnea-hypopnea index; AHI, and oximetry indices) [19].…”
Section: Related Workmentioning
confidence: 66%
“…However, there is a paucity of research investigating the relationship between sleep microarchitecture and the future development of hypertension in OSA. Berger et al recently reported that low delta power in non-REM sleep is independently associated with the risk of developing hypertension, confirming the previously noted relationship of SWS with incident hypertension [18]. Another study relied on complex feature engineering to examine 27 unselected clinical predictors, encompassing demographic characteristics, lifestyle behaviors, and OSA severity (apnea-hypopnea index; AHI, and oximetry indices) [19].…”
Section: Related Workmentioning
confidence: 66%
“…It is noteworthy that the association between sleep duration (both objectively measured and subjectively reported) and hypertension has been a topic of debate in the literature (5)(6)(7)(8)(9)(10). Furthermore, certain studies have indicated that factors such as sleep efficiency, sleep quality, sleep microstructure, and fragmented sleep may also play a role in the development of hypertension (11)(12)(13)(14)(15), and poor subjective sleep quality assessed by the Pittsburgh Sleep Quality Index (PSQI) was demonstrated an association with the incidence of hypertension (16). Sleep stages as objective sleep characteristics in humans are divided into rapid eye movement (REM) sleep and non-rapid eye movement (NREM) sleep.…”
Section: Introductionmentioning
confidence: 99%